Influences of Spillway Section Morphologies on Landslide Dam Breaching - Yang, Meng; Zhong, Qiming; Mei, Shengyao; Shan, Yibo (Frontiers in Earth Science, 2021)
Abstract: Spillway excavation is often adopted as a precautionary engineering measure for disaster mitigation before landslide dam breaching. Nevertheless, the influences of spillway section types on the landslide dam breach processes have yet to be elucidated. This paper focuses on developing a numerical model to comprehensively discuss the influences of spillway section types on breach hydrograph and breach size evolution. Three landslide dam failures with detailed breach information, Tangjiashan, Xiaogangjian, and Baige landslide dams, were chosen as representatives. The spillway cross section types were modeled with different sizes under common shape (i.e., an inverted trapezoid) and slope conditions. The influence on dam breach processes was analyzed under conditions of different depth, bottom width, slope ratio in the cross and longitudinal sections, with/without spillway. The calculated results show that excavation of a spillway has a significant impact on the breach process, can effectively reduce the peak breach flow, therefore delay the time to peak. For the morphological parameters in the excavation of spillway, spillway depth is the most important influencing factor on breach process; the peak breach flow and the time to peak delays as the spillway depth increases. The spillway bottom width has a major impact on the time to peak; the peak breach flow occurs earlier with the increment in spillway bottom width. Also, with the decrease of slope ratio in cross section in the spillway, the peak breach flow decreases, while the time to peak delays. The slope ratio in the longitudinal section has little influence on the breach process. For the landslide dam with the structure of coarse particles at the upper layer and fine particles at the bottom layer, the landslide dam would not fail without a spillway if the hydrodynamic conditions are weak; however, the risk of dam failure is still existing. Hence, for the landslide dam with large dam height and water storage, spillway excavation is an effective risk mitigation method; if conditions permit, the spillway with large spillway depth, small bottom width, and gentle slope ratio in the cross section is the preferable section type for the emergency disposal of the landslide dam.